IL-1β Promotes TGF-β1 and IL-2 Dependent Foxp3 Expression in Regulatory T Cells - Ganesh, Balaji B. (Public Library of Science, 2011)
Earlier, we have shown that GM-CSF-exposed CD8α− DCs that express low levels of pro-inflammatory cytokines IL-12 and IL-1β can induce Foxp3+ Tregs leading to suppression of autoimmunity. Here, we examined the differential effects of IL-12 and IL-1β on Foxp3 expression in T cells when activated in the presence and absence of DCs. Exogenous IL-12 abolished, but IL-1β enhanced, the ability of GM-CSF-exposed tolerogenic DCs to promote Foxp3 expression. Pre-exposure of DCs to IL-1β and IL-12 had only a modest effect on Foxp3− expressing T cells; however, T cells activated in the absence of DCs but in the presence of IL-1β or IL-12 showed highly significant increase and decrease in Foxp3+ T cell frequencies respectively suggesting direct effects of these cytokines on T cells and a role for IL-1β in promoting Foxp3 expression. Importantly, purified CD4+CD25+ cells showed a significantly higher ability to maintain Foxp3 expression when activated in the presence of IL-1β. Further analyses showed that the ability of IL-1β to maintain Foxp3 expression in CD25+ T cells was dependent on TGF-β1 and IL-2 expression in Foxp3+Tregs and CD25− effectors T cells respectively. Exposure of CD4+CD25+ T cells to IL-1β enhanced their ability to suppress effector T cell response in vitro and ongoing experimental autoimmune thyroidits in vivo. These results show that IL-1β can help enhance/maintain Tregs, which may play an important role in maintaining peripheral tolerance during inflammation to prevent and/or suppress autoimmunity.